Analisis Kesalahan Siswa dalam Menyelesaikan Soal Matematika pada Materi Sistem Persamaan Linear Tiga Variabel Kelas X SMAN 1 Cisaat - Dikri Maulana Azis; Hamidah Suryani Lukman; Nur Agustiani (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2018)
This study’s aim is to find out and describe the types of class X student error IPA 1 SMA Negeri 1 Cisaat as well as solutions to solve student error on linear equation system material three variables. The type of research used in this study was the type of descriptive qualitative research. The location of this research was in SMA Negeri 1 Cisaat. This study took the subject of research as many as four students with the technique of taking the subject by purposive sampling. Data analysis techniques conducted in this research are data reduction, data presentation, and conclusion. After the data were analyzed then validated the validity of the data by using technique triangulation, that is by comparing the result of the student's answer on test questions and interview result. The results obtained from this study are the type of concept mistakes made the subject of research on misconceptions reached 32.26%. Then the type of procedural error is a mistake that is often done by the subject of research, procedure error reached 48.39%. Therefore, the type of error in using the operation or calculation as much as 19.35%.